KONTROVERSI PENGIBARAN BENDERA BINTANG KEJORA DI ISTANA NEGARA DALAM PERSPEKTIF HUKUM PIDANA - Nurfadilah Nurfadilah; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The raising of the Morning Star flag at the State Palace by Papuan students caused a lot of controversy in various aspects, because some people thought that the Papuan students' actions were treasonous but there were also those who thought that it did not include treason. The purpose of this research is to find out the actions taken by Papuan students have included the crime of treason and to find out whether or not there are reasons for the elimination of crimes in the name of democracy. The type of this research is normative legal research based on library research using secondary data. This research uses qualitative analysis and produces descriptive data.From the results of the research, the authors conclude that from the perspective of criminal law, the actions of Papuan students, namely conducting demonstrations with one of the demands, namely wanting to separate themselves from the territory of the Unitary State of the Republic of Indonesia accompanied by the raising of the Morning Star flag are included in the crime of treason. because in this case it has fulfilled the elements of treason in Article 106 of the Criminal Code. In addition, there is no reproach to provide reasons for the abolition of crimes to these Papuan students, because considering the state is in a state of danger so that the state can free itself from its obligations and responsibilities towards human rights and this is in line with Article 28J Paragraph 2 of the 1945 Constitution of the Republic of Indonesia in order to achieve the territorial integrity of Indonesia.The author's suggestion is for the government to immediately form a new norm regarding the crime of treason, in order to provide clarity in the formulation of the criminal act of treason in the Criminal Code, to the Papua Provincial government to immediately form a Special Regional Regulation regarding regional symbols in Papua, and it is hoped that the government can again allow the flying. the Morning Star flag as regulated by the previous Gusdur administration and in order to revise the Government Regulation on Regional Symbols by not including the Morning Star flag as a symbol of the separatist movement, considering that the Morning Star flag is a cultural flag by the Papuan people.Keywords: Crime of Treason-Bintang Kejora Flag-Papuan Students